ANALYSIS OF THE EFFECTIVENESS OF LEARNING ACTIVITIES AND LEARNING MOTIVATION ON STUDENTS' LEARNING ACHIEVEMENT DURING THE COVID 19 PANDEMIC (CASE STUDY AT THE FACULTY OF BUSINESS ECONOMICS, WIDYATAMA UNIVERSITY) - Athallah, Mochamad Ridho; Rahmat, Habib Triyadi; Gustira, Ikhsan Fawwaz; Raafi, Duigary Muhammad; Arofah, Arief Bidjak Nur; Santoso, Anton Budi (CENTRAL ASIA AND THE CAUCASUS, 2022)
This study aims to determine how much influence the effectiveness of learning and learning motivation has on learning achievement during the Covid 19 pandemic at Widyatama University. Due to the Covid-19 outbreak, the learning model that was previously carried out face-to-face learning has now changed to online learning. The population in this study were active students of the Faculty of Economics and Business, Widyatama University batch 2018 and 2019 as many as 1,484 people, with a sample of 80 people. This study uses a descriptive method with a quantitative approach. The data collection technique uses primary data, in the form of a survey using a questionnaire with the google form platform. This research employs multiple linear regression analysis methods for data processing and analysis techniques. SPSS version 20.0 program is used to calculate the data. The results show that the effectiveness of learning and student motivation has a significant effect on student achievement. Learning methods that have changed to online are less effective that it reduces student learning motivation and have an impact on student achievement.